Understanding the risk perception of visceral leishmaniasis exposure and the acceptability of sandfly protection measures among migrant workers in the lowlands of Northwest Ethiopia: a health belief model perspective - Resom Berhe; Mark Spigt; Francine Schneider; Lucy Paintain; Cherinet Adera; Adane Nigusie; Zemichael Gizaw; Yihenew Alemu Tesfaye; Dia-Eldin A. Elnaiem; Mekuriaw Alemayehu (BMC, 2022)
Abstract Background Visceral leishmaniasis (VL) is the leading cause of health concerns among Ethiopian migrant workers. Understanding risk perception and health-protective behavior are significant challenges in the prevention and eradication of the disease. As a result, studies are required to assess these important epidemiological factors, which will provide guidance on how to assist migrant workers in taking preventive measures against VL. Method We conducted qualitative research among migrant workers on seasonal agricultural farms in Northwest Ethiopia between June and November 2019 to assess their perception of the risk of contracting VL and their willingness to use protective measures against the disease. Seventeen focus group discussions and 16 key informant interviews were conducted to study migrant workers' risk perception in relation to sandfly bite exposure and use of sandfly control measures. For analysis, all interviews were recorded, transcribed, and translated. ATLASti was used to perform qualitative content analysis on the data. Result Migrant workers are fearful of VL because of previous exposure and the disease's prevalence in the area. They believe, however, that VL is a minor illness that is easily treated. While Insecticide Treated Nets (ITNs) are widely accepted as a protective measure, there are still reservations about using them due to the seasonality of the transmission, difficulties in hanging them on farm areas, and a preference for alternative traditional practices. Regardless of perceived self-efficacy, the central cues were the message delivered by the health workers and an increase in sandfly bite irritation. Based on the findings, three levels of intervention modalities are suggested: 1) increasing pre-arrival awareness through outdoor media (posters, stickers, billboards), 2) encouraging proper use of protective measures upon arrival at farm camps, and 3) informing departing workers on disease recognition and best practices for health-seeking continuous use of protective measures at home. Conclusion This finding suggests that VL prevention interventions should focus on individuals' perceptions in order to promote consistent use of protective measures. The findings are highly useful in planning effective interventions against VL.